Geliat Politik Islam Lokal di Indonesia Tahun 1998-2021: Studi Politik Islam Daerah Kediri, Aceh dan Sumenep - Azizah T, Ratih Himamatul (Prodi Sosiologi Agama, 2021)
This article examines Islamic political governance in Indonesia. Islamic political revival began in the reform era. Reform era provides democratic space for national political parties and local political parties in exploring democracy in the regions. Islamic politics in the region has different forms in carrying it out and does not lose the side of locality because it is in accordance with the socio-cultural conditions of the local community. Islamic politics in kediri by adjusting the socio-cultural condition the people tidak kagetan so that the form of Islamic politics kediri is an tolerant. Politics Islamic in sumenep etnic islam politics with the philosophy “bhuppa’, bhabu’, guru, rato” the from of leadership respect the kiai as a teacher and rules. Islamic politics in aceh with characteristics maintains Islamic politics in accordance with Allah provisions.